2017
DOI: 10.1515/cclm-2016-0382
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Preanalytical Quality Monitoring Program (SEQC), an overview of 12 years’ experience

Abstract: For the majority of sample types, a decrease in preanalytical errors was confirmed. Improvements in organization, implementation of standardized procedures in the preanalytical phase, and participation in a Spanish external quality assessment scheme may have notably contributed to error reduction in this phase.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…Consistent with our findings, the Spanish Preanalytical Quality Monitoring Program found that nonreceived samples (34.5%, 37.5%) and hemolysis (29.3%, 36.2%) are the most frequent cause of serum sample rejections for the span of 12 years. [ 17 ] In another study, nonreceived samples (25.5%) were reported as the major preanalytical errors. [ 18 ] This error is a process indicator that provides data on sample collection since nonreceived samples will prompt a new request for sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our findings, the Spanish Preanalytical Quality Monitoring Program found that nonreceived samples (34.5%, 37.5%) and hemolysis (29.3%, 36.2%) are the most frequent cause of serum sample rejections for the span of 12 years. [ 17 ] In another study, nonreceived samples (25.5%) were reported as the major preanalytical errors. [ 18 ] This error is a process indicator that provides data on sample collection since nonreceived samples will prompt a new request for sample collection.…”
Section: Discussionmentioning
confidence: 99%
“…The rates were similar to Llopis's study, which stated the rate of incorrect container as 0.013% and 0.009% for two time periods. 23 Sample not received was the least frequent error and also showed a significant decrease. However, the studies in Spain and in the USA indicated the rates were much higher of 0.23% and 0.01%, respectively.…”
Section: Qis On Specimen Rejection In Laboratories In Zhejiang Provinmentioning
confidence: 92%
“…21 Llopis et al stated sample rejection due to clotting was 0.054% in Spanish pre-analytical quality monitoring program. 23 The main cause of clotting is directly related to the blood collection process and attributed to human factors, such as absence of standardized collection procedure, insufficient mixing after blood withdrawal, and prolonged storage. 24,25 The greatest magnitude of decrease was observed for the rate of incorrect sample type.…”
Section: Qis On Specimen Rejection In Laboratories In Zhejiang Provinmentioning
confidence: 99%
“…The results of the QC, in terms of how many events of control are out of the acceptability limits compared with the total QC events, provide for the likelihood of detection of a failure in the process. Similarly, there have been developed QC programs for the preanalytical phase (Florin, Oyaert, Van Maerken, & Devreese, 2018; Kristensen, Moberg Aakre, Kristoffersen, & Sandberg, 2014; Llopis et al, 2016).…”
Section: Discussionmentioning
confidence: 99%